ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI SWASTA DI JAWA TENGAH (JEJAK, 2008)
Investment very significant influence economic growth, this research aim to identify and analysefactors influencing private invesment in Central Java Province. Analyse use multiple regression modelwith Ordinary Least Square method (OLS). Result of analyse indicate that, rate of interest negativeinfluence and significant to private invesment in Central Java coefficient –1017.464. Governmentexpenditure and inflation have positive influence and significant to private invesment in Central Javacoefficient 243.715 and 0.19.Keywords: private invesment, rate of interest, government expenditure and inflation